The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s0885-3924(00)00144-5
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Fatigue in Lymphoma Patients Treated With High Dose Therapy

Abstract: With the success of high dose therapy supported by autologous bone marrow transplantation (ABMT) for malignant lymphomas, medical late-effects and secondary effects on subjective health, like fatigue, are of concern. Fatigue is poorly understood and correlates have been barely addressed. Health-related quality of life (HRQL), fatigue, and correlates to fatigue, including endocrinological status and serum levels of interleukin-6, tumor necrosis factor, and soluble tumor necrosis factor receptors, were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
5
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 41 publications
3
54
5
2
Order By: Relevance
“…This is also consistent with other studies, and fatigue is beginning to be recognised as one of the most significant and long-term consequences of cancer and its treatment (Hann et al, 1997;Hann et al, 1999;Knobel et al, 2000;Okuyama et al, 2001). Of note is that almost half of all patients who were identified as suffering significant distress had not used psychosocial resources in the past or present, and did not intend to use the services in the future.…”
Section: Discussionsupporting
confidence: 89%
“…This is also consistent with other studies, and fatigue is beginning to be recognised as one of the most significant and long-term consequences of cancer and its treatment (Hann et al, 1997;Hann et al, 1999;Knobel et al, 2000;Okuyama et al, 2001). Of note is that almost half of all patients who were identified as suffering significant distress had not used psychosocial resources in the past or present, and did not intend to use the services in the future.…”
Section: Discussionsupporting
confidence: 89%
“…However, in most studies, no associations were found between tumor-related variables and fatigue intensity with regard to disease duration [23,25,26,29,[33][34][35], type of cancer [27,36], disease stage at diagnosis [23, 25-27, 33, 37], size of the original tumor [25,26,37], number of nodes involved [25] and tumor recurrence [33].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found no association between circulating levels of IL-1β and fatigue, although it should be noted that the levels of IL-1β in this report were extremely high (mean = 1,152pg/ml, range = 9 -3, 952pg/ml), well above levels seen in other groups of cancer patients and healthy individuals. Two other studies examined inflammatory parameters among patients with hematological malignancies who had completed treatment at least 3 months previously (Dimeo et al, 2004;Knobel et al, 2000). Neither study found an association between fatigue and markers of inflammation, including serum levels of IL-1β, IL-1ra, IL-6, neopterin, CRP, and the soluble TNF receptors.…”
Section: Fatigue and Inflammation In Cancer Survivorsmentioning
confidence: 99%